Multiple Choice Questions Analysis in the Textbook of Al-Qur'an Hadith MI Class I Published by the Ministry of Religious Affairs in 2020 - Ridho Budi Utomo; Muhammad Ali; Roby Salim; Bambang Samsul Arifin; Mulyawan Safwandy Nugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study analyses the proportion of multiple-choice questions in the categories of Higher Order Thinking Skills (HOTS) and Lower Order Thinking Skills (LOTS) in the Al-Qur'an Hadith MI Class I textbook published by the Ministry of Religious Affairs in 2020. Using qualitative methods through document study and Milles and Huberman analysis, this study found that 96% of the questions were classified as LOTS (L1/C1, L1/C2, L2/C3), while HOTS was only 4%. This finding shows that the book has not met the 21st century learning standards that emphasize the importance of HOTS. This result confirms that there is a need for curriculum revision and improvement of question quality to be more in line with modern learning standards.